Incidence of ovarian endometrioma among women with peritoneal endometriosis with and without a history of hormonal contraceptive use. (August 2017) - Kavoussi, Shahryar K.; Odenwald, Kate C.; As-Sanie, Sawsan; Lebovic, Dan I.
Abstract: Objective(s): To determine if, among women with peritoneal endometriosis, the incidence of ovarian endometrioma at first laparoscopy differs between those with and without a history of hormonal contraceptive use. Study design: Retrospective case-control study of women who were patients at a fertility center and had first laparoscopy from 2009 through 2015 showing, at minimum, evidence of peritoneal endometriosis (n = 136). Chart review was conducted for history of prior birth control use as well as operative and pathology notes of surgeries. Study subjects were grouped as follows: women with peritoneal endometriosis diagnosed by laparoscopy who had a history of hormonal contraceptive use (n = 93) and women with peritoneal endometriosis diagnosed by laparoscopy who had never used hormonal contraceptives (n = 43). The main outcome measure was the incidence of ovarian endometrioma among women with peritoneal endometriosis who had a history of hormonal contraceptive use as compared to women with peritoneal endometriosis who had a history of no hormonal contraceptive use. Results: Among women with peritoneal endometriosis who had a history of hormonal contraceptive use, 17/93 (18.3%) were found to have endometriomas. Among women with peritoneal endometriosis who had a history of no hormonal contraceptive use, 21/43 (48.8%) were found to have endometriomas. The chi-square statistic was 13.6 (P-value < 0.001). Conclusion(s): Among women with peritoneal endometriosis, those with a history of hormonal contraceptive use had a lower incidence of ovarian endometrioma than those with a history of no hormonal contraceptive use. Possible mechanisms of action include reducing the risk of a corpus luteum formation and subsequent transformation into an ovarian endometrioma or reducing the risk of ectopic endometrium implantation into the ovary via the diminution of retrograde menstruation. Although larger, prospective studies are needed, the findings of this study suggest that the use of hormonal contraception may decrease the likelihood of ovarian endometrioma formation among women with peritoneal endometriosis.